THE VARIETIES OF HOMEWORK GIVEN BY ENGLISH TEACHERS OF VOCATIONAL SCHOOLS - Dinar Martia Azizah (Indonesian EFL Journal, 2018)
Learning inside the classroom is never enough because there are various limitations, so it needs the non-school hour assignment called homework. This research aims to find out the varieties of homework given by English teachers of vocational schools. This research uses a qualitative descriptive method by involving eight English teachers of vocational schools in Yogyakarta. Open-ended questionnaires, interview, and document analysis are used to collect the data. In analyzing the obtained data, the researcher does three steps, namely data condensation, data display, and conclusion drawing. The research results showed that homework varieties given by English teachers serve three main objectives. Those objectives are to broaden knowledge, sharpen skills, and inculcate values. It is concluded that formal education in schools requires homework that improve students' English proficiency. Besides, the existence of State Examination is regarded as a special thing that effects on learning process.Keywords: homework; broaden knowledge; sharpen skills; inculcate values; English proficiency.